A Most Novel Continuity: Correlating the Theologies of History of Bernard Lonergan and Henri de Lubac - Schlesinger, Eugene R. (Theological studies, 2024)
In terms of their interests and methodologies, Bernard Lonergan and Henri de Lubac seem at first blush to be incommensurable worlds apart. Closer examination shows their basic positions on the theology of history to be not only compatible but also complementary. Both place Christ’s redemptive act as the constitutive meaning of history, with all that follows as the expansion of this act through Christ’s Mystical Body. De Lubac’s account of Christ as the bestower of novel meaning provides a more intensive christological focus to Lonergan’s construal of the unified continuity of human agency. Lonergan, in turn, provides greater theoretical controls of meaning to the Lubacian account.